2017
DOI: 10.1038/s41598-017-03154-5
|View full text |Cite
|
Sign up to set email alerts
|

Differential depression of neuronal network activity by midazolam and its main metabolite 1-hydroxymidazolam in cultured neocortical slices

Abstract: The benzodiazepine midazolam is widely used in critical care medicine. Midazolam has a clinically active metabolite, 1-hydroxymidazolam. The contribution of 1-hydroxymidazolam to the effects of midazolam is controversial. The aim of the current study was to compare the actions of midazolam and 1-hydroxymidazolam on network activity of cortical neurons. Midazolam depressed neuronal activity at a low concentration of 5 nM. When midazolam concentration was increased, it depressed neuronal discharge rates in a bip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…The effect of antegrade amnesia, combined with opioids, etomidate, propofol drugs can produce synergistic or additive effects, resulting in analgesic effect. 27 , 28 Previous studies have found that midazolam could shorten sleep latency, reduce wakefulness frequency, improve objective sleep evaluation and reduce daytime sleepiness. 29 However, some scholars have also pointed out that long-term application of benzodiazepines could lead to an increase of shallow sleep and increased risk of adverse effects such as cognitive impairment and falling, especially in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of antegrade amnesia, combined with opioids, etomidate, propofol drugs can produce synergistic or additive effects, resulting in analgesic effect. 27 , 28 Previous studies have found that midazolam could shorten sleep latency, reduce wakefulness frequency, improve objective sleep evaluation and reduce daytime sleepiness. 29 However, some scholars have also pointed out that long-term application of benzodiazepines could lead to an increase of shallow sleep and increased risk of adverse effects such as cognitive impairment and falling, especially in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…The observed increase in exposure to the active metabolite 1′‐OH‐MDZ may therefore be due to CBD‐mediated inhibition of UGTs, in particular UGT2B7 22 . The increase in exposure to 1′‐OH‐MDZ with concomitant CBD could potentially increase the effects of MDZ in cases of impaired drug metabolism or when MDZ is administered at high doses 43 . The clinical relevance of the increase in exposure to 1′‐OH‐MDZ when MDZ is administered with CBD is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Because midazolam is a short-acting water-soluble benzodiazepine sedative, midazolam produces sedative, hypnotic, anticonvulsant, and anxiolytic effects by altering the configuration of the GABAA receptor complex and opening the chloride channel. The effect of antegrade amnesia, combined with opioids, etomidate, propofol drugs can produce synergistic or additive effects, resulting in analgesic effect (17). However, the use of midazolam can accumulate in patients with renal failure, and some patients may also develop drug resistance; while the excessive injection dose or use may cause blood pressure drop or respiratory depression in patients with hypovolemia (18).…”
Section: Discussionmentioning
confidence: 99%